The Sixth Man - Baldacci, David; McLarty, Ron.; Cassidy, Orlagh; Hachette Audio (Firm) (New York : Hachette Audio, 2011)
Sean King and Michelle Maxwell are shocked to discover attorney Ted Bergin murdered. He was working on a case involving a serial killer, but as King and Maxwell dig deeper, they discover the case to be infinitely more complicated. Their persistence puts them on a collision course with the highest levels of the government and the darkest corners of power.
Abridged.
Sequel to the author's First family.
Compact disc.
In container (17 cm.).
Read by Ron McLarty and Orlagh Cassidy.
Keywords: Serial murder investigation -- Fiction; Psychiatric hospital patients -- Fiction; Private investigators -- Fiction; Mystery fiction; Suspense fiction; Audiobooks